Intralingual Variation in Acceptability Judgments and Production: Three Case Studies in Russian Grammar - Gerasimova, Anastasia; Lyutikova, Ekaterina (Frontiers in Psychology, 2020)
This paper contributes to the task of defining the relation between the results of production and rating experiments in the context of language variation. We address the following research question: how may the grammatical options available to a single speaker be distributed in the two domains of production and perception? We argue that previous studies comparing acceptability judgments and frequencies of occurrence suffer from significant limitations. We approach the correspondence of production and perception data by adopting an experimental design different from those used in previous research: (i) instead of using a corpus we use production data obtained experimentally from respondents who are later asked to make judgments, (ii) instead of pairwise phenomena we examine language variation, (iii) judgments are collected formally using the conditions and materials from the production experiment, (iv) we analyze the behavior of each participant across the production and acceptability judgment experiments. In particular, we examine three phenomena of variation in Russian: case variation in nominalizations, gender mismatch, and case variation in paucal constructions. Our results show that there is substantial alignment between acceptability ratings and frequency of occurrence. However, frequencies and acceptability scores do not always coincide in their distribution. Speakers are not consistent in choosing a single variant across the two types of experiment. Importantly, the types of inconsistency they display differ, which means that the variation can be characterized from this point of view. We conclude that the degree of coherence of the two experiments reflects the effects of the evolution of variation over time. Another result is that elicited production and acceptability judgments vary with respect to how they reveal variation in language. In the case of the development or disappearance of variants, production indicates this earlier than judgments, and the rating task has the effect of restricting the choice available to respondents. However, the production method should not thereby be considered more sensitive. We argue that only a combination of production and judgment data makes it possible to estimate the directionality of changes in variability and to see the full distribution of different variants.